2018
DOI: 10.3389/fpsyg.2018.01278
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Timescales in Perspective-Taking

Abstract: Through theoretical discussion, literature review, and a computational model, this paper poses a challenge to the notion that perspective-taking involves a fixed architecture in which particular processes have priority. For example, some research suggests that egocentric perspectives can arise more quickly, with other perspectives (such as of task partners) emerging only secondarily. This theoretical dichotomy–between fast egocentric and slow other-centric processes–is challenged here. We propose a general vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 109 publications
3
29
0
Order By: Relevance
“…The influence of partner models in HMD may therefore not be absolute, but granular, with more egocentric production processes also at play in interaction. This echoes recent findings on the role of other-centric and egocentric processes in dialogue [20,21].…”
Section: The Impact Of Accent On Partner Models and Lexical Choicesupporting
confidence: 88%
“…The influence of partner models in HMD may therefore not be absolute, but granular, with more egocentric production processes also at play in interaction. This echoes recent findings on the role of other-centric and egocentric processes in dialogue [20,21].…”
Section: The Impact Of Accent On Partner Models and Lexical Choicesupporting
confidence: 88%
“…The current findings revealed that consistency in ToM-use cannot be taken for granted. This echoes recent work which suggests that the context and saliency of the cues associated with self and other could alter the ways in which perspectives are inferred and considered over the course of an interaction [ 32 34 ]. Additionally, a conversational partner and their social relationship with the listener could determine the degrees to which listeners are motivated to take their partner’s perspective into account [ 35 ].…”
Section: Discussionsupporting
confidence: 67%
“…The consistency in performance across the two body alignment conditions may reflect the robustness of perspective-taking as a behavior that emerges from different processes accumulating information at different interacting timescales (Dale et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Tollefsen & Dale, 2012;Dale, et al, 2018) and potentially task performance. For example, in direction giving, the task partners' body alignment in space can support conceptual alignment by providing a simple global cue (Brennan, Galati, & Kuhlen, 2010) for how to represent the partner's perspective in the immediate task environment (e.g., "same perspective as mine"), while linguistic and behavioral alignment exhibited as partners respond contingently to one another can support conceptual alignment through the emergence of local routines (e.g., the re-use of expressions from a route perspective, tracking the navigator's path).…”
Section: Relative Body Alignment Grounding and Coordinationmentioning
confidence: 99%